2012
DOI: 10.1177/1088357612457986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Observing-Response Procedures on Overselectivity in Individuals With Autism Spectrum Disorders

Abstract: Stimulus overselectivity occurs when one aspect of the environment controls behavior at the expense of other equally salient aspects. Stimulus overselectivity can be reduced for some individuals with learning disabilities, if they engage in an observing response in which they point to, touch, or name each of the stimuli prior to selecting the one requested. To see whether this would apply to another population, a total of 55 participants with autism spectrum disorders (ASD) were trained on match-to-sample (MTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…The results of Study 1 correspond to the only other study of which we are aware that examined DOR effects under simple discrimination contingencies (Reed et al., 2012). In this study, DORs did not facilitate simple stimulus control over pointing responses of participants diagnosed with ASD.…”
Section: Discussionsupporting
confidence: 77%
“…The results of Study 1 correspond to the only other study of which we are aware that examined DOR effects under simple discrimination contingencies (Reed et al., 2012). In this study, DORs did not facilitate simple stimulus control over pointing responses of participants diagnosed with ASD.…”
Section: Discussionsupporting
confidence: 77%
“…It is fortunate that stimulus overselectivity and blocking may be reduced by teaching an overt precurrent ("observing") response to the S + (Doughty & Hopkins, 2011), as well as by teaching conditional discrimination from the beginning of a procedure, rather than following a simple discrimination (Green, 2001). Moreover, Farber et al (2017) suggested that differential observing responses (e.g., different tacts to sample stimuli) during matching-to-sample resulted in less overselectivity than nondifferential observing responses, where the response to the sample is the same on every trial, in children with autism (e.g., Reed, Altweck, Broomfield, Simpson, & McHugh, 2012). Differential observing responses verify the discrimination of stimulus features that differ among the samples (e.g., by tacting the sample stimuli).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, eye-tracking data from individuals with intellectual disabilities suggest that overselected stimuli (i.e., those exerting selective control) are observed more often and for longer durations than underselected stimuli (i.e., those exerting little to no control). Additionally, interventions that differentially reinforce observing of underselected stimuli appear to remediate overselectivity, although their effects may not necessarily maintain over time (Dube & McIlvane, 1999;Dube et al, 2003Dube et al, , 2010Farber et al, 2017;Walpole et al, 2007; but see also Reed, Altweck, et al, 2012).…”
mentioning
confidence: 99%